Pemanfaatan Air Gambut untuk Berwudu dalam Perspektif Fikih Taharah - Syamsiah Nur; Sartini La Mbajo; Anastasya Putri (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study aims to introduce one type of water in Indonesia, namely peat water and its use for ablution in the perspective of taharah fiqh. This research is a library research that focuses on the study of manuscripts and texts, using a normative and descriptive juridical approach. In analyzing the data, the researcher used content analysis. The results of this study are peat water that has not been processed, the law can be permissible, makruh or forbidden to use for ablution. It is permissible to use peat water whose pH and organic matter can still be categorized as normal, but it is makruh if it is used long term as a form of caution. If it has been processed into clean water, it is legal to use it for ablution even though the taste, color and smell have changed by taking into account the increasing demand for clean water. The legal decisions that have been made have not taken into account the adaptability that the community around peat water may have.